Behavioral Counseling in Relaxation Techniques in Primigravida TM III: a Module Development - Widhyani, Agung; Suranata, Kadek; Gading, I Ketut (Bisma The Journal of Counseling, 2020)
This research was conducted to be able to provide a behavioral counseling module with relaxation techniques to Primigravida TM III mothers where it is hoped that Primigravida TM III mothers can relax in facing the process of pregnancy and childbirth later. This type of research is Research and Development (R & D), the research model used is Four-D (4 D). The 4D model consists of four stages, namely: define, design, develop and disseminate, but dissemination is not carried out due to the COVID 19 pandemic. Analysis to test the validity of the instrument using the Lawshe CVR and CVI formulas by testing. by 5 experts in their expert fields, namely Guidance and Counseling Experts, Psychology Experts and Health Experts from both educational institutions and Health service providers (Midwives Independent Practice). The results showed that the CVR score was 21.6 and the CVI score was 0.9818, so the content of the product was important and based on data analysis, the value of the product content validity in the form of a behavioral counseling module in Trimester III primigravida was high and significant.